Investigation of the Role of Serum Matrix Gla-Protein as a Biomarker of Calcific Aortic Valve Disease - Amal Al Nawasreh; HussamShebli; Sahar Fahoum (Journal of Pharmacy and Nutrition Sciences, 2019)
Background: Calcific aortic valve disease (CAVD) is a major contributor to cardiovascular morbidity and mortality. Circulating total uncarboxylated Matrix ?-carboxyglutamate (Gla) protein (t-ucMGP) is a promising biomarker for rapid screening of subjects prone to cardiovascular calcification who may need more invasive vascular diagnostics. Preliminary data show that low t-ucMGP levels are indicative for prevalent vascular calcification. Hence, the aim of our study was to investigate the possible role of circulating t-ucMGP as a biomarker may help in identification patients with CAVD, taking into consideration that CAVD is a form of vascular calcification. Methods & Materials: We analyzed serum t-ucMGP levels by enzyme-linked immunosorbent assay (ELISA) in 50 patients with echocardiographically proven CAVD and 21 control subjects. Results: Serum t-ucMGP levels were significantly lower in patients with CAVD (29.29±12.18 nmol/l) compared to the control group (36.84±21.79 nmol/l, p = 0.003). Conclusion: Serum t-ucMGP may help as a noninvasive biomarker for identification of these patients.